An efficient exfoliation method of MXene materials prepared by molten salt method
Patent Information
- Application Number
- CN202410726641.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-06-06
AI Technical Summary
然而,氟刻蚀的方法采用了含氟蚀剂,使得MXene端基组成含有氟元素,影响MXene在储能和生物医药等方面的应用
[0035]1、本发明创造性地将电化学插层及超声处理相结合的剥离方法应用于熔盐法制备的MXene材料的剥离,实现了熔盐法制备的MXene材料的高效率剥离,获得高产率的少层MXene;
Smart Images

Figure CN118561281B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new materials technology and relates to an efficient exfoliation method for MXene materials prepared by molten salt method. Background Technology
[0002] MXene, a novel two-dimensional material, is primarily composed of transition metal carbon and / or nitrides. Its intrinsic nanolayered structure, large specific surface area, good hydrophilicity, excellent electrical conductivity, and catalytic activity make it a promising candidate for applications in numerous fields, including chemical sensing, supercapacitors, photocatalysts, transparent conductive films, electronic devices, energy, and flexible high-strength composite materials. Furthermore, its superior electronic properties give MXene excellent electrochemical charge storage capabilities, making it a preferred electrode material for electrochemical energy storage devices such as supercapacitors and lithium-ion batteries.
[0003] Chemical etching is currently a relatively mature technology for preparing MXene materials, mainly including fluorine etching and Lewis acid molten salt etching. However, fluorine etching uses fluorine-containing etchants, resulting in fluorine inclusions in the end groups of MXene, which affects its applications in energy storage and biomedicine. Molten salt etching avoids the introduction of fluorine and allows for targeted control of the end groups; however, MXene created by molten salt etching is currently difficult to exfoliate efficiently, hindering its application. Achieving efficient exfoliation of MXene created by molten salt etching is a bottleneck in its application, and solving this problem is crucial for promoting its widespread use. Summary of the Invention
[0004] To address the aforementioned problems in the prior art, the present invention aims to provide an efficient exfoliation method for MXene materials prepared by the molten salt method, thereby overcoming the shortcomings of the prior art.
[0005] One objective of this invention is achieved through the following technical solution:
[0006] An efficient exfoliation method for MXene materials prepared by molten salt method includes the following steps:
[0007] S1. The MXene material prepared by the molten salt method is pressed into a sheet as the working electrode and assembled with the counter electrode, the diaphragm and the electrolyte to form a two-electrode system. The electrolyte includes lithium salt and propylene carbonate (PC).
[0008] S2. Connect the assembled two electrodes to the electrochemical workstation and perform constant current discharge;
[0009] S3. After the discharge is complete, remove the working electrode, clean it, and centrifuge it to obtain the precipitate;
[0010] S4. The precipitate is added to a solvent to form a dispersion and then subjected to ultrasonic treatment.
[0011] S5. After ultrasonic treatment, the suspension is centrifuged, the supernatant is collected, and the MXene membrane is obtained by vacuum filtration.
[0012] Preferably, the molecular formula of the MXene material prepared by the molten salt method is M n+1 X n T x Where M is one or more elements in groups 3, 4, 5, 6 or 7 of the periodic table, X is C and / or N, T is a surface functional group, and n is 1, 2 or 3.
[0013] Further preferred, M is one or more of Ti, V, Nb, Mn, Y, Zr, Cr, Mo, Hf, Ta, W, and Sc.
[0014] More preferably, T includes one or more of -Cl, -Br, -I, -F, -O, -OH, -S, alkyl, alkoxy, ether, and ester groups.
[0015] Further optimization yielded MXene material M4X3Cl. x M4X3Br x M3X2Cl x M3X2Br x M2XCl x or M2XBr x .
[0016] The object to be stripped is MXene material prepared by molten salt method, which is prepared by etching MAX phase material by Lewis acid molten salt method, including the following steps: mixing MAX phase material, Lewis acid salt and inorganic salt, reacting at high temperature, removing excess salt and impurities, drying, and obtaining MXene material prepared by molten salt method.
[0017] Preferably, the molecular formula of the MAX phase material is M n+1 AX n In this context, element M is the same as element M in the molecular formula of MXene material, element X is the same as element X in the molecular formula of MXene material, the value of n is the same as the value of n in the molecular formula of MXene material, and A is one or more elements from group IIIA or IVA of the periodic table.
[0018] Preferably, the Lewis acid salt is a Lewis acid salt including the target functional group, including but not limited to transition metal halides. Examples include one or more of FeCl2, CoCl2, NiCl2, CuCl2, ZnCl2, SnCl2, CdCl2, FeBr2, CoBr2, NiBr2, CuBr2, ZnBr2, SnBr2, CdBr2, FeI2, CoI2, NiI2, CuI2, CdI2, and AgI.
[0019] Preferably, the inorganic salt is a metal halide salt formed by a halogen element and a metal element. The metal element can be one or more of Na, K, Li, Mg, Ca, etc., and the halogen element can be one or more of F, Cl, Br, I. The inorganic salt includes, but is not limited to, any one or more of LiCl, NaCl, KCl, LiBr, NaBr, KBr, LiI, KI, and NaI.
[0020] Preferably, the high-temperature reaction temperature is any temperature capable of melting Lewis acid salts and inorganic salts. For example, the high-temperature reaction temperature is 400–900°C, and the high-temperature reaction time is 1–10 h.
[0021] Preferably, the MXene material prepared by the molten salt method is pressed into sheets with a diameter of 1 to 50 mm, further with a diameter of 5 to 30 mm, and further with a diameter of 10 to 20 mm.
[0022] Preferably, the counter electrode is a lithium metal sheet with a diameter of 1–50 mm, further having a diameter of 5–30 mm, and further having a diameter of 10–20 mm.
[0023] Preferably, the diaphragm is one or more of polyolefin membranes (such as polypropylene membranes, polyethylene membranes), polyester membranes, polyimide membranes, polyamide membranes, cellulose membranes, etc., and the diaphragm diameter is 1-50 mm, more preferably 5-30 mm, and more preferably 10-20 mm.
[0024] Preferably, in the above method, the electrolyte is a propylene carbonate solution of LiTFSI with a concentration of 0.1–10 mol / L, more preferably 0.5–5 mol / L.
[0025] Preferably, in the above method, the current density of constant current discharge is 1 to 50 mA / g, more preferably 10 to 30 mA / g; the discharge termination voltage is 0.005 to 1 V, more preferably 0.01 to 0.5 V.
[0026] Preferably, in the above method, the precipitate is placed in a solvent for ultrasonic treatment, the solvent being water, an alcohol solvent, a ketone solvent, etc.; an ultrasonic probe is placed in the dispersion for ultrasonic treatment, the ultrasonic power being 100-1000W, more preferably 200-800W; the ultrasonic treatment time being 20-300min, more preferably 30-200min; and the diameter of the ultrasonic probe being 1-10mm.
[0027] Preferably, in the above method, the ultrasonic treatment is performed under ice-water bath conditions.
[0028] Preferably, in the above method, the centrifugation speed in step S5 is 2000-8000 rpm, and the centrifugation time is 10-60 min.
[0029] Preferably, the filter membrane used for vacuum filtration is an aqueous filter membrane with a pore size of 1–50 μm.
[0030] Preferably, the obtained few-layer MXene accounts for 55–95 wt% of the MXene material prepared by the molten salt method. Further, the obtained few-layer MXene accounts for 90–93 wt% of the MXene material prepared by the molten salt method.
[0031] Few-layer MXene refers to a stacked structure containing two to dozens of MXene sheets.
[0032] The second objective of this invention is achieved through the following technical solution:
[0033] A few-layer MXene membrane, which is prepared by the above-described exfoliation method.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. This invention creatively applies a peeling method combining electrochemical intercalation and ultrasonic treatment to the peeling of MXene materials prepared by the molten salt method, achieving high-efficiency peeling of MXene materials prepared by the molten salt method and obtaining high-yield few-layer MXene.
[0036] 2. This invention uses an electrolyte comprising lithium salt and propylene carbonate to effectively weaken the van der Waals effect of MXene during constant current discharge and to expand the interlayer spacing of MXene. Furthermore, under the action of ultrasound, it achieves efficient exfoliation of MXene prepared by the molten salt method, with a yield of up to 92.57 wt% for few-layer MXene.
[0037] 3. The stripping method of the present invention has the characteristics of high yield, low risk and easy implementation. Compared with the traditional stripping process, which may involve harsh conditions such as high temperature, strong acid and strong oxidant, the present invention is safer and more reliable. Attached Figure Description
[0038] Figure 1 The images show the XRD patterns of few-layer Ti3C2Cl2 and multi-layer Ti3C2Cl2 in Embodiment 1 of the present invention.
[0039] Figure 2 The images shown are SEM (a), TEM (b), and AFM (c) images of a single few-layer Ti3C2Cl2 particle from Example 1 of this invention.
[0040] Figure 3 Optical image (a) and cross-sectional SEM image (b) of the few-layer Ti3C2Cl2 film prepared in Example 1 of the present invention;
[0041] Figure 4 The images show comparisons of the stripping processes of Examples 1 and Comparative Examples 1-4 using different electrolytes. (a) is an optical comparison of the dispersions after stripping with different electrolytes in Examples 1 and Comparative Examples 1-4, and (b) is an XRD comparison of the filtered products after stripping with different electrolytes in Examples 1 and Comparative Examples 1-4. Detailed Implementation
[0042] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.
[0043] Example 1
[0044] The exfoliation method for Ti3C2Cl2 MXene prepared by the molten salt method in this embodiment is as follows:
[0045] (1) Preparation of Ti3C2Cl2 MXene by molten salt method: Ti3AlC2 powder, CdCl2 powder, NaCl and KCl of MAX phase material were thoroughly ground and mixed in a molar ratio of 1:3:10:10 to obtain a mixed powder. The mixed powder was placed in an alumina crucible and then placed in a high-temperature vacuum tube furnace and reacted at 650℃ for 5h under an inert atmosphere (argon). After the sintering temperature dropped to room temperature, the alumina crucible was removed. The reaction product was washed with water and 3mol / L hydrochloric acid solution to remove excess salt and the generated Cd metal element, respectively. The product was filtered and dried under vacuum at 80℃ for 4h to obtain Ti3C2Cl2 MXene powder prepared by molten salt method.
[0046] (2) The Ti3C2Cl2 MXene prepared by molten salt method was pressed into a sheet with a diameter of 14 mm as the working electrode, the lithium metal with a diameter of 14 mm as the counter electrode, and the PP membrane with a diameter of 16 mm as the battery separator. 200 μL of the prepared lithium-ion electrolyte was added to assemble the two electrodes. The lithium-ion electrolyte was a 1 mol / L LiTFSI PC solution.
[0047] (3) Connect the assembled two electrodes to the electrochemical workstation and perform constant current discharge. The current density is 10 mA / g and the discharge termination voltage is 0.01 V.
[0048] (4) Disassemble the two electrodes after the discharge is complete, take out the MXene electrode that has been discharged, wash it with acetone and alcohol respectively, centrifuge it twice, and collect the precipitate.
[0049] (5) The washed precipitate was added to 40ml of water to form a dispersion. The dispersion was ultrasonically treated for 1 hour using an ultrasonic probe with a power of 500W (the diameter of the ultrasonic probe is 6mm) under the condition of cooling in an ice water bath.
[0050] (6) The ultrasonically treated suspension was centrifuged at 6000 rpm for 30 minutes, and the supernatant was collected. This process of centrifugation was used to separate the few-layer and multi-layer MXenes.
[0051] (7) Take the upper layer liquid and filter it. The filter membrane used for filtration is Celgard 3501 membrane to obtain a few layers of Ti3C2Cl2MXene membrane.
[0052] Figure 1 The images show the XRD patterns of few-layer Ti3C2Cl2 and multi-layer Ti3C2Cl2 in Example 1. From the perspective of interlayer spacing, the interlayer spacing of few-layer Ti3C2Cl2 is greatly improved compared to that of multi-layer Ti3C2Cl2, exhibiting typical few-layer characteristics. Furthermore, the few-layer Ti3C2Cl2 crystal structure obtained by the stripping method of this embodiment is complete.
[0053] Figure 2 SEM (a), TEM (b), and AFM (c) images of single few-layer Ti3C2Cl2 particles prepared in Example 1 (the above images were obtained by observing the few-layer dispersion droplets on the membrane). Figure 2 (a)-2(c) all clearly show that the prepared material is a few-layer Ti3C2Cl2.
[0054] Only a few layers of MXenes can be extracted into a flexible membrane; multiple layers of MXenes are particles that cannot be stacked together and cannot form a membrane. Figure 3 (a) is an optical image of the few-layer Ti3C2Cl2 film prepared in Example 1. Figure 3(b) is a cross-sectional SEM image of the few-layer Ti3C2Cl2 film, from... Figure 3 The film formation is good, indicating that a few-layer Ti3C2Cl2 has been prepared.
[0055] Example 2
[0056] The only difference between Example 2 and Example 1 is that the discharge termination voltage in step (3) of Example 2 is 0.5V.
[0057] Example 3
[0058] The exfoliation method for Ti3C2Br2 MXene prepared by the molten salt method in this embodiment is as follows:
[0059] (1) Preparation of Ti3C2Br2 MXene by molten salt method: Ti3AlC2 powder, CdBr2 powder, NaCl and KCl of MAX phase material were thoroughly ground and mixed in a molar ratio of 1:3:10:10 to obtain mixed powder; the mixed powder was placed in an alumina crucible and then placed in a high-temperature vacuum tube furnace and reacted at 650℃ for 12h under an inert atmosphere (argon). After the sintering temperature dropped to room temperature, the alumina crucible was removed; the reaction product was washed with water and 3mol / L hydrochloric acid solution to remove excess salt and the generated Cd metal element, respectively, filtered, and dried under vacuum at 80℃ for 4h to obtain Ti3C2Br2 MXene powder prepared by molten salt method.
[0060] (2) Ti3C2Br2 MXene prepared by molten salt method is pressed into a sheet with a diameter of 14 mm as the working electrode, lithium metal with a diameter of 14 mm is used as the counter electrode, and PP membrane with a diameter of 16 mm is used as the battery separator. 200 μL of prepared lithium-ion electrolyte is added to assemble the two electrodes; the lithium-ion electrolyte is a 1 mol / L LiTFSI PC solution.
[0061] (3) Connect the assembled two electrodes to the electrochemical workstation and perform constant current discharge. The current density is 10 mA / g and the discharge termination voltage is 0.01 V.
[0062] (4) Disassemble the two electrodes after the discharge is complete, take out the MXene electrode that has been discharged, wash it with acetone and alcohol respectively, centrifuge it twice, and collect the precipitate.
[0063] (5) The washed precipitate was added to 40ml of water to form a dispersion. The dispersion was ultrasonically treated for 1 hour using an ultrasonic probe with a power of 500W (the diameter of the ultrasonic probe is 6mm) under the condition of cooling in an ice water bath.
[0064] (6) The ultrasonically treated suspension was centrifuged at 6000 rpm for 30 minutes, and the supernatant was collected. This process of centrifugation was used to separate the few-layer and multi-layer MXenes.
[0065] (7) Take the upper layer liquid and filter it. The filter membrane used for filtration is Celgard 3501 membrane to obtain a few layers of Ti3C2Br2MXene membrane.
[0066] Example 4
[0067] The exfoliation method for Ti2CClx (0 < x ≤ 2)MXene prepared by the molten salt method in this embodiment is as follows:
[0068] (1) The MAX phase materials Ti2AlC powder, CdCl2 powder, NaCl and KCl were thoroughly ground and mixed in a molar ratio of 1:3:10:10 to obtain a mixed powder. The mixed powder was placed in an alumina crucible and then placed in a high-temperature vacuum tube furnace and reacted at 700℃ for 4h under an inert atmosphere (argon). After the sintering temperature dropped to room temperature, the alumina crucible was removed. The reaction product was washed with water and 3mol / L hydrochloric acid solution to remove excess salt and the generated Cd metal element, filtered, and dried under vacuum at 80℃ for 4h to obtain Ti2CClx MXene powder.
[0069] (2) Ti2CClx MXene prepared by molten salt method is pressed into a sheet with a diameter of 16 mm as the working electrode, lithium metal with a diameter of 16 mm as the counter electrode, and PP membrane with a diameter of 18 mm as the battery separator. 200 μL of prepared lithium-ion electrolyte is added to assemble the two electrodes; the lithium-ion electrolyte is a 0.8 mol / L LiTFSI PC solution.
[0070] (3) Connect the assembled two electrodes to the electrochemical workstation and perform constant current discharge. The current density is 5 mA / g and the discharge termination voltage is 0.01 V.
[0071] (4) Disassemble the two electrodes after the discharge is complete, take out the MXene electrode that has been discharged, wash it with acetone and alcohol respectively, centrifuge it twice, and collect the precipitate.
[0072] (5) The washed precipitate was added to 50 ml of water to form a dispersion. The dispersion was ultrasonically treated for 50 min using an ultrasonic probe with a power of 600 W (the diameter of the ultrasonic probe is 6 mm) under the condition of cooling in an ice water bath.
[0073] (6) The ultrasonically treated suspension was centrifuged at 5000 rpm for 40 minutes, and the supernatant was collected. This process of centrifugation was used to separate the few-layer and multi-layer MXenes.
[0074] (7) Take the upper layer liquid and filter it. The filter membrane used for filtration is Celgard 3501 membrane to obtain a few layers of Ti2CClxMXene membrane.
[0075] Example 5
[0076] The stripping method for V2CClx (0 < x ≤ 2)MXene prepared by the molten salt method in this embodiment is as follows:
[0077] (1) The MAX phase materials V2AlC powder, CdCl2 powder, NaCl and KCl were thoroughly ground and mixed in a molar ratio of 1:3:10:10 to obtain a mixed powder. The mixed powder was placed in an alumina crucible and then placed in a high-temperature vacuum tube furnace and reacted at 700°C for 5 hours under an inert atmosphere (argon). After the sintering temperature dropped to room temperature, the alumina crucible was removed. The reaction products were washed with water and 3 mol / L hydrochloric acid solution to remove excess salt and the generated Cd metal element, filtered, and dried under vacuum at 80°C for 4 hours to obtain V2CClx MXene powder.
[0078] (2) The V2CClx MXene prepared by molten salt method was pressed into a sheet with a diameter of 14 mm as the working electrode, the lithium metal with a diameter of 14 mm as the counter electrode, and the PP membrane with a diameter of 16 mm as the battery separator. 300 μL of the prepared lithium-ion electrolyte was added to assemble the two electrodes. The lithium-ion electrolyte was a 1.2 mol / L LiTFSI PC solution.
[0079] (3) Connect the assembled two electrodes to the electrochemical workstation and perform constant current discharge. The current density is 8 mA / g and the discharge termination voltage is 0.01 V.
[0080] (4) Disassemble the two electrodes after the discharge is complete, take out the MXene electrode that has been discharged, wash it with acetone and alcohol respectively, centrifuge it twice, and collect the precipitate.
[0081] (5) The washed precipitate was added to 60ml of water to form a dispersion. The dispersion was ultrasonically treated for 2 hours using an ultrasonic probe with a power of 400W (the diameter of the ultrasonic probe is 6mm) under the condition of cooling in an ice water bath.
[0082] (6) The ultrasonically treated suspension was centrifuged at 7000 rpm for 30 minutes, and the supernatant was collected. This process of centrifugation was used to separate the few-layer and multi-layer MXenes.
[0083] (7) Take the upper layer liquid and filter it. The filter membrane used for filtration is Celgard 3501 membrane to obtain a few layers of V2CClx MXene membrane.
[0084] Example 6
[0085] The Nb₂CCl prepared by the molten salt method in this embodiment x The stripping method for (0 < x ≤ 2)MXene is as follows:
[0086] (1) The MAX phase materials Nb2AlC powder, CuCl2 powder, NaCl, and KCl were thoroughly ground and mixed in a molar ratio of 1:3:10:10 to obtain a mixed powder. The mixed powder was placed in an alumina crucible and then placed in a high-temperature vacuum tube furnace and reacted at 650℃ for 6 hours under an inert atmosphere (argon). After the sintering temperature dropped to room temperature, the alumina crucible was removed. The reaction product was washed with water and 0.1 mol / L APS (ammonium persulfate) solution to remove excess salt and the generated Cu metal element, respectively. The product was filtered and dried under vacuum at 80℃ for 5 hours. x MXene powder.
[0087] (2) Preparation of Nb2CCl by molten salt method x MXene was pressed into a sheet with a diameter of 14 mm as the working electrode, lithium metal with a diameter of 14 mm as the counter electrode, and a PP membrane with a diameter of 16 mm as the battery separator. 300 μL of prepared lithium-ion electrolyte was added to assemble the two electrodes. The lithium-ion electrolyte was a 1.5 mol / L LiTFSI PC solution.
[0088] (3) Connect the assembled two electrodes to the electrochemical workstation and perform constant current discharge. The current density is 20mA / g and the discharge termination voltage is 0.01V.
[0089] (4) Disassemble the two electrodes after the discharge is complete, take out the MXene electrode that has been discharged, wash it with acetone and alcohol respectively, centrifuge it twice, and collect the precipitate.
[0090] (5) The washed precipitate was added to 40ml of water to form a dispersion. The dispersion was ultrasonically treated for 1.5 hours under the cooling condition of an ice-water bath using an ultrasonic probe with a power of 550W (the ultrasonic probe diameter is 6mm).
[0091] (6) The ultrasonically treated suspension was centrifuged at 6000 rpm for 40 minutes, and the supernatant was collected. This process of centrifugation was used to separate the few-layer and multi-layer MXenes.
[0092] (7) The supernatant was filtered using a Celgard 3501 membrane to obtain a few layers of Nb2CCl. x MXene membrane.
[0093] The few-layer MXene yields of Examples 1-6 were calculated, and the results are shown in Table 1:
[0094] Few-layer MXene yield = Few-layer MXene film obtained by peeling ÷ Multilayer MXene used during tableting.
[0095] Table 1. Few-layer MXene yields in Examples 1-6
[0096]
[0097]
[0098] As shown in Table 1, the few-layer MXene yields obtained in Examples 1-2 are as high as 90 wt% or more, and the few-layer MXene yields obtained in Examples 3-4 are greater than 55%, indicating that the method of the present invention has very high stripping efficiency. Examples 1 and 2 show that the lower the final discharge voltage, the higher the few-layer MXene yield.
[0099] Comparative Example 1
[0100] The difference between Comparative Example 1 and Example 1 is that in step (2) of Comparative Example 1, the lithium-ion electrolyte is a 1 mol / L LiTFSI dimethyl sulfoxide (DSMO) solution, while the rest is the same as in Example 1. The product is labeled as DMSO-Ti3C2Cl2.
[0101] Comparative Example 2
[0102] The difference between Comparative Example 2 and Example 1 is that in step (2) of Comparative Example 2, the lithium-ion electrolyte is a 1 mol / L LiTFSI dimethyl carbonate (DMC) solution, while the rest is the same as in Example 1. The product is labeled as DMC-Ti3C2Cl2.
[0103] Comparative Example 3
[0104] The difference between Comparative Example 3 and Example 1 is that in step (2) of Comparative Example 3, the lithium-ion electrolyte is a 1 mol / L LiTFSI acetonitrile (ACN) solution, while the rest is the same as in Example 1. The product is labeled ACN-Ti3C2Cl2.
[0105] Comparative Example 4
[0106] The difference between Comparative Example 4 and Example 1 is that in step (2) of Comparative Example 4, the lithium-ion electrolyte is a 1 mol / L LiTFSI solution of 2-methyltetrahydrofuran (2Me-THF), while the rest is the same as in Example 1. The product is labeled as 2Me-THF-Ti3C2Cl2.
[0107] Figure 4(a) is an optical comparison image of the dispersions after stripping with different electrolytes in Example 1 and Comparative Examples 1-4. It can be seen that no obvious precipitation was observed in the dispersions obtained after stripping with PC-based electrolyte, indicating that the dispersions were well dispersed. Figure 4 (b) is a comparison of the XRD patterns of the filtered products after stripping with different electrolytes in Example 1 and Comparative Examples 1-4. It can be seen that the sample obtained by stripping with PC-based electrolyte is a few-layer MXene with a complete crystal structure.
[0108] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0109] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.
[0110] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. A highly efficient exfoliation method for MXene materials prepared by molten salt method, characterized in that, Includes the following steps: S1. The MXene material prepared by the molten salt method is pressed into a sheet as the working electrode and assembled with the counter electrode, the separator, and the electrolyte to form a two-electrode system. The counter electrode is a lithium metal sheet, and the electrolyte includes lithium salt and propylene carbonate. S2. Connect the assembled two electrodes to the electrochemical workstation and perform constant current discharge. The current density of the constant current discharge is 1~50 mA / g, and the discharge termination voltage is 0.005~1 V. S3. After the discharge is complete, remove the working electrode, clean it, and centrifuge it to obtain the precipitate; S4. The precipitate is added to a solvent to form a dispersion and then subjected to ultrasonic treatment. The ultrasonic power is 100~1000 W, the ultrasonic treatment time is 20~300 min, and the diameter of the ultrasonic probe is 1~10 mm. S5. After ultrasonic treatment, the suspension is centrifuged, the supernatant is collected, and the MXene membrane is obtained by vacuum filtration.
2. The method according to claim 1, characterized in that, The object to be stripped is MXene material prepared by the molten salt method, which is obtained by etching MAX phase material using Lewis acid molten salt method, including the following steps: MXene prepared by the molten salt method is obtained by mixing MAX phase material, Lewis acid salt and inorganic salt, reacting at high temperature, removing excess salt and impurities, and drying.
3. The method according to claim 1, characterized in that, The MXene material prepared by the molten salt method is pressed into sheets with a diameter of 1~50 mm to serve as the working electrode; the lithium metal sheet has a diameter of 1~50 mm.
4. The method according to claim 1, characterized in that, The diaphragm is one or more of the following: polyolefin membrane, polyester membrane, polyimide membrane, polyamide membrane, and cellulose membrane, and the diameter of the diaphragm is 1 to 50 mm.
5. The method according to claim 1, characterized in that, The electrolyte is a LiTFSI propylene carbonate solution with a concentration of 0.1~10 mol / L.
6. The method according to claim 1, characterized in that, The ultrasonic probe was placed in the dispersion for ultrasonic treatment, which was carried out under ice-water bath conditions.
7. The method according to claim 1, characterized in that, In step S5, the centrifugation speed is 2000~8000 rpm and the centrifugation time is 10~60 min.
8. The method according to claim 1, characterized in that, The few-layer MXene film obtained accounted for 55-95 wt% of the MXene material prepared by the molten salt method.
9. A few-layer MXene membrane prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Electrochemical method for preparing MXene material through accurate etching of molten salt
CN117658140A